2016
DOI: 10.1162/jocn_a_00901
|View full text |Cite
|
Sign up to set email alerts
|

Phonological Processing in Primary Progressive Aphasia

Abstract: Individuals with primary progressive aphasia (PPA) show selective breakdown in regions within the proposed dorsal (articulatory-phonological) and ventral (lexical-semantic) pathways involved in language processing. Phonological short-term memory impairment, which has been attributed to selective damage to dorsal pathway structures, is considered to be a distinctive feature of the logopenic variant of PPA. By contrast, phonological abilities are considered to be relatively spared in the semantic variant and are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
68
0
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 84 publications
(80 citation statements)
references
References 48 publications
8
68
0
4
Order By: Relevance
“…The lvPPA group showed reduced activation of posterior superior temporal cortex in response to phonemic spectral structure. These syndromic signatures are in accord with prior predictions concerning the informational components of speech signals that are most likely to be vulnerable in each PPA syndrome (Golden et al., 2015, Grube et al., 2016, Hailstone et al., 2012, Hardy et al., 2015, Henry et al., 2016, Hsieh et al., 2011, Lambon Ralph et al., 2010, Rohrer et al., 2010). Performance on post-scan behavioral testing correlated with regional neural activation for the processing of phonemic structure and signal information content for the relevant syndromic (lvPPA and svPPA) groups relative to healthy controls: functional neuroanatomical profiles may therefore underpin behavioral speech processing deficits in these syndromes, though the lack of correlation within the respective patient groups suggests that additional factors may drive individual performance variation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The lvPPA group showed reduced activation of posterior superior temporal cortex in response to phonemic spectral structure. These syndromic signatures are in accord with prior predictions concerning the informational components of speech signals that are most likely to be vulnerable in each PPA syndrome (Golden et al., 2015, Grube et al., 2016, Hailstone et al., 2012, Hardy et al., 2015, Henry et al., 2016, Hsieh et al., 2011, Lambon Ralph et al., 2010, Rohrer et al., 2010). Performance on post-scan behavioral testing correlated with regional neural activation for the processing of phonemic structure and signal information content for the relevant syndromic (lvPPA and svPPA) groups relative to healthy controls: functional neuroanatomical profiles may therefore underpin behavioral speech processing deficits in these syndromes, though the lack of correlation within the respective patient groups suggests that additional factors may drive individual performance variation.…”
Section: Discussionmentioning
confidence: 99%
“…These mechanisms are bi-hemispherically distributed and left hemisphere specialization may be in part directed by connectivity changes under linguistic tasks (Leaver and Rauschecker, 2010, Markiewicz and Bohland, 2016, Obleser et al., 2010, Zhang et al., 2016). This interpretation also accords with the differential activation profiles shown by the present patient groups on the relevant phonemic contrast: compared with healthy controls, the nfvPPA and svPPA groups showed relatively normal activation profiles, whereas the lvPPA group exhibited a significantly attenuated response to natural phonemes in the key superior temporal region, in line with the clinical deficits of phonological processing (Gorno-Tempini et al., 2008, Grube et al., 2016, Hailstone et al., 2012, Hardy et al., 2015, Henry et al., 2016, Rohrer et al., 2010) and related deficits of paralinguistic analysis (Rohrer et al., 2012) previously documented in lvPPA. Although we did not assess working memory directly in this experiment, posterior superior temporal cortex has been shown to play an integral role in auditory working memory for phonemes as well as other auditory objects (Kumar et al., 2016, Markiewicz and Bohland, 2016), suggesting that the profile identified here is relevant to the phonological working memory impairment that is a defining feature of lvPPA (Gorno-Tempini et al., 2008, Gorno-Tempini et al., 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Patients with the non-fluent/agrammatic variant of PPA were impaired in inflecting pseudowords, which we anticipated due to the phonological deficits that have been documented in this variant (Patterson et al, 2006a; Ash et al, 2010; Wilson et al, 2010b; Henry et al, in prep). Affixing a suffix to a novel word form and selecting the appropriate allomorph are phonological processes that lack lexical support and thus are challenging for patients with phonological impairments, and we found that in the PPA group as a whole, inflection of pseudowords was strongly predicted by a phonological composite measure.…”
Section: Discussionmentioning
confidence: 92%
“…Sensitivity to the syntactic factor of finiteness suggests that deficits in inflectional morphology in non-fluent/agrammatic PPA may follow from syntactic deficits. Phonological deficits may also contribute, since non-fluent patients have been shown to produce phonemic paraphasias in connected speech (Patterson, Graham, Lambon Ralph, & Hodges, 2006a; Ash et al, 2010; Wilson et al, 2010b) and to exhibit difficulties on phonological manipulation tasks (Patterson et al, 2006a; Henry et al, in prep). Logopenic PPA is associated with core phonological and word-finding deficits (Gorno-Tempini et al, 2004, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Phonological skills in patients with PPA have been studied by several authors. Recently, Henry et al confirmed the critical role of dorsal stream structures in phonological processing, demonstrating unique patterns of impaired phonological processing in patients with lv-PPA [18]. In another study, Leyton et al studied a series of patients with lv-PPA reporting that naming deficits were associated with thinning of the left inferior parietal lobe, while sentence repetition impairment correlated with a loss of volume of the left superior temporal gyrus.…”
Section: Discussionmentioning
confidence: 99%